Perbedaan Ukuran Gigi Molar Pertama Maksila dan Kaninus Mandibula Permanen Antara Mahasiswa Laki-laki dan Perempuan di FKG Universitas Jember - Najla Irhamni Phasa; Dwi Kartika Apriyono; Masniari Novita (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Mass disaster often happened in Indonesia. Sex identification is one of the important things for determining the identity of the victims. Sex can be identified based on the size of the teeth. The study determine the differences of maxillary first molar and mandibular caninus tooth size between male and female student in Faculty of Dentistry University of Jember. The sample of this study consisted of 34 tooth models of female and 6 tooth models of male that measured in mesiodistal and bucolingual width of maxillary first molar and mandibular caninus with a digital caliper. Data were analyzed using Independent T-test. There were significant differences (p ≤ 0,05) of maxillary first molar and mandibular caninus size between male and female. Mesiodistal and bucolingual width of maxillary first molar respectively are 10.64 mm, 11.90 mm in males, and 10.16 mm, 11.16 mm in females. The mesiodistal and bucolingual width of mandibular caninus are 7.13 mm, 7.85 mm in males, and 6.66 mm, 7.08 mm in females. It can be concluded that there was a difference in size of maxillary first molar and mandibular caninus between male and female. Keywords: sex identification, masiodistal width, bucolingual width, maxillary first molar, mandibular caninus